PENAPISAN FITOKIMIA DAN PENENTUAN KADAR FLAVONOID EKSTRAK DAUN SEMBUNG [BLUMEA BALSAMIFERA (L.) DC] DI DESA HASANG DAN DESA SIMANGALAM KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA - masdingin naipospos; Muhammad Idris; Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Sembung [Blumea balsamifera (L.) DC] is a medicinal plant that contains secondary metabolites. Differences in geographical location, climate, morphology and plant parts used can affect the content of secondary metabolites and the levels of flavonoids produced. The purpose of this study was to analyze the presence of secondary metabolites and flavonoid levels in sembung leaf extract from Hasang and Simangalam villages. The method used is to observe and observe samples in the field and identify the presence of secondary metabolites and flavonoid levels through laboratory tests. Extraction is done by the maceration method. Flavonoid testing was carried out qualitatively (phytochemical screening test, KLT test) and quantitative (Test levels with UV-Vis spectrophotometry ). The results showed that sembung plants from Hasang and Simangalam villages were positive for flavonoids, saponins and steroids. The KLT test for flavonoid compounds in Hasang village on N-hexane : ethyl acetate resulted in 3 spots and on Chloroform : ethyl acetateÂ  8 spots for flavonoid compounds. Extract from Simangalam village on N-hexane : ethyl acetate resulted in 8 spots and Chloroform : ethyl acetate produced 19 spots for flavonoid compounds.Â  The result showed that the flavonoid content of sembung leaf extract from Hasang village was 89,2971 mg QE/g, which was higher than the flavonoid content from Simangalam village was 83,9828 mg QE/g.